Estrategias pedagógicas y su incidencia en la utilización de materiales didácticos en el subnivel II de la Unidad Educativa Armando Pareja Coronel - Ayala Moreira, Pamela Prisila (2023)
The present work of curricular integration Pedagogical strategies and their incidence in the use of didactic materials in Sublevel II of the Armando Pareja Coronel Educational Unit of the Mata de Cacao parish. Its objective is to analyze the pedagogical strategies and their incidence in the use of didactic materials in Sublevel II, for its fulfillment a methodology was used that consisted of a non-experimental design, field and documentary research, mixed approach, inductive and deductive method Interview and observation techniques were also applied with their respective investigative instruments, which were directed to a sample of 29 students and two sublevel 2 teachers obtained through a non-probabilistic sampling. The results were: teachers occasionally use videos in their classes and digital tools; the educators images and ludic activities (songs and rounds) to help the assimilation of contents; a significant group of children rarely have interest and motivation for the content presented in educational videos or slides; most children almost always develop creativity and imagination when handling blocks and play dough. As conclusions, pedagogical strategies are of great importance in Sublevel II of education, since they have a significant impact on the effective use of teaching materials, which facilitate children's learning and help them develop abilities and skills. The pedagogical strategies used by the teacher are audiovisual, playful strategies and supported by digital tools. The didactic materials that are used in the educational process of Sublevel II consist of educational videos, projection of images, blocks, plasticine and slides.